Resposta eletrofisiológica e comportamental em crianças e adolescentes usuários de aparelho de amplificação sonora individual - Folgearini, Jordana da Silva (2018)
The objective of this study was to obtain the Electrophysiological and Behavioral Minimum Response Levels (MRL) for speech sounds, to evaluate the language performance (vocabulary) and auditory behavior of children and adolescents with Hearing Impairment (HI), according to the variables ear, degree of HI and period of installation of HI. This study was of the quantitative, descriptive, cross-sectional type. The sample arrangement consisted of convenience, in which 22 children and adolescents between the ages of three and 18 years old, of both genders, with mild to severe HI from Hearing Health Program of the Public Health System were evaluated. The procedures for sample composition were: database search, anamnesis, external auditory meatus inspection, tonal threshold audiometry, logoaudiometry, and acoustic immitance measurements. Regarding the collection procedures, the following were recorded: Cortical Auditory Evoked Potential (CAEP), Ling Sounds Detection Test, Children's Nomination Test (CNT) and Auditory Behavior in Everyday Life (ABEL) questionnaire. There was no significant difference between ears for the electrophysiological response. There was a correlation between the electrophysiological and behavioral MRL for the phonemes /m/, /u/, /a/ and /i/ of the pre-verbal group. There was a correlation between electrophysiological MRL and degree of HI, as well as between the behavioral MRL and HI degrees for all phonemes, with the exception of /s/. There was no correlation between electrophysiological MRL and time of auditory deprivation, language performance and auditory behavior. It was possible to obtain electrophysiological and behavioral MRL, and these were correlated in some variables in the pre-verbal group. The children with lower degree of loss obtained the lowest electrophysiological and behavioral MRL. The deprivation time, vocabulary measurement, and family perception of auditory behavior were not correlated with electrophysiological MRL in the sample.